The Application of PDCA Nursing Mode in the Case of a Patient with Dentition Defect Undergoing Dental Implantation: A Case Study - Wu, Dan; Huang, Zefan; Zhang, Jiali; Hong, Xiaoying; Sun, Haipeng; Wu, Binbin; Zhou, Ruantong (International Journal of Public Health and Medical Research, 2024)
This study summarizes the nursing experience of dental implant restoration in a patient with cerebral palsy and dentition defect. We applied the PDCA nursing mode throughout the patient’s treatment process and observed significant positive outcomes. The surgery and nursing care proceeded smoothly, with the patient’s neurological functions remaining stable postoperatively. The dental implant showed good osseointegration, healthy surrounding soft tissues, and no signs of bone loss in radiographic examinations. The patient’s oral hygiene remained consistent. This case highlights the effectiveness of the PDCA nursing mode in improving nursing quality, promoting patient recovery, and reducing complications in patients with dentition defects and cerebral palsy undergoing dental implant surgery. This approach holds significant clinical implications and merits wider adoption.